Nontuberculous Mycobacteria in Cystic Fibrosis in the Era of Cystic Fibrosis Transmembrane Regulator Modulators - Burke, Andrew; Thomson, Rachel M.; Wainwright, Claire E.; Bell, Scott C. (Seminars in Respiratory and Critical Care Medicine, 2023)
Nontuberculous mycobacteria (NTM) are a group of mycobacteria which represent opportunistic pathogens that are of increasing concern in people with cystic fibrosis (pwCF). The acquisition has been traditionally though to be from environmental sources, though recent work has suggested clustered clonal infections do occur and transmission potential demonstrated among pwCF attending CF specialist centers. Guidelines for the screening, diagnosis, and identification of NTM and management of pwCF have been published. The emergence of CF-specific therapies, in particular cystic fibrosis transmembrane regulator (CFTR) modulator drugs, have led to significant improvement in the health and well-being of pwCF and may lead to challenges in sampling the lower respiratory tract including to screen for NTM. This review highlights the epidemiology, modes of acquisition, screening and diagnosis, therapeutic approaches in the context of improved clinical status for pwCF, and the clinical application of CFTR modulator therapies.
Keywords: cystic fibrosis; nontuberculous mycobacteria; Mycobacterium abscessus; Mycobacterium avium complex; CFTR modulator; epidemiology; environmental exposure